Lay perceptions of mental health among Afghan forced migrants residing in Finland - Farahani, Hadi; Martikainen, Jari; Golamrej Eliasi, Laleh; Tavakol, Mohamed; Toikko, Timo (Routledge, 2025)
This study explores lay perceptions of mental health among Afghan forced migrants in Finland. Semi-structured interviews were conducted with 25 participants. Reflexive thematic analysis was used as the method of analysis. The analysis produced two main themes: external symptoms (changes in physical appearance and behavior) and internal symptoms (burdensome feelings and sensations). Participants rarely used explicit mental health terminology, preferring nuanced culture-specific, individual expressions, and indirect communication about stress and trauma. This study contributes to the understanding of Afghan forced migrants’ lay perceptions of mental health and calls for culturally-safe approaches in social work and mental health services for forced migrants.